TEACHERSâ AND STUDENTSâ PERCEPTIONS OF MOTIVATIONAL TEACHING STRATEGIES IN AN INDONESIAN HIGH SCHOOL CONTEXT - Sri Puji Astuti (TEFLIN, 2013)
The primary purpose of this multiple case study is to explore teachersâ and learnersâ perceptions of motivational teaching strategies. The data were obtained from two schools in a small town in West Sumatra, Indonesia; one is from an international standard high school and the other is from a local high school. This study is underpinned by Dornyeis (2001) work on motivational teaching practice which consists of four phases on how a teacher motivates students in a language learning classroom, namely: creating motivational components, generating studentsâ motivation, maintaining motivation, and encouraging positive retrospective self-evaluation. This qualitative case study is intended to contextualise the research within the real life environment of an Indonesian secondary class- room (Yin, 2003). The findings indicate that there are two groups of motivational components. The first is the teachersâ rapport with students, including the encouragement given to students and the building of trust and respect with the students. The second relates to the teachersâ planning decisions such as the selection of classroom activities, the way feedback is given, the management of the classroom, and the choice of learning resources.Â